1988
DOI: 10.1097/00002093-198802010-00025
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric differentiation of dementia. Replication and extension of the findings of Storandt and coworkers

Abstract: \s=b\In a previous investigation by Storandt

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…With the latter a correct classification rate of 65.9% was obtained. This accuracy rate is somewhat lower than the results obtained by some studies that used a multivariate approach, albeit a more comprehensive neuropsychological battery, to differentiate DAT from VD patients [77% in Barr et al (1992), 74% in Perez et al (1995)] but similar to other studies [58% to 76% in Parlato et al (1988) and 70% in Tierney et al (1987)] using the same statistical method.…”
Section: Resultssupporting
confidence: 44%
“…With the latter a correct classification rate of 65.9% was obtained. This accuracy rate is somewhat lower than the results obtained by some studies that used a multivariate approach, albeit a more comprehensive neuropsychological battery, to differentiate DAT from VD patients [77% in Barr et al (1992), 74% in Perez et al (1995)] but similar to other studies [58% to 76% in Parlato et al (1988) and 70% in Tierney et al (1987)] using the same statistical method.…”
Section: Resultssupporting
confidence: 44%
“…Three other studies have previously shown that`mental control' from the Wechsler Memory Scale, which includes counting backwards from 20, was an important test for diagnosing of dementia (Storandt et al, 1984;Tierney et al, 1987Tierney et al, , 1996, and attention, as measured by the two CAMCOG subtests, has been identi®ed as a predictor of dementia 5 years prior to the diagnosis (Brayne et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The test is reported to distinguish mild dementia from healthy aging. 19 The DSST score is calculated as the total number of items correctly coded in 90 seconds, with a higher score indicating better cognitive function.…”
Section: Methods Study Populationmentioning
confidence: 99%